Experimental and Theoretical Research on Shear Strength of Seismic-Damaged SRC Frame Columns Strengthened with Enveloped Steel Jackets - Chengxiang C. X. Xu; Peng S. Sheng; Chong C. Wan (Advances in Civil Engineering)
The experimental and shear strength analytical investigations carried out on seismic-damaged steel reinforced concrete (SRC) columns strengthened with enveloped steel jacket subjected to cyclic loading are presented in this paper. Four 1/2-scale SRC columns were designed and manufactured and the postearthquake damage, enveloped steel jacket-confined, and destructive tests were carried out under lateral cyclic loading. The effects of postearthquake damage degree and enveloped steel jacket-confined on shear capacity and ductility capacity were all well examined. Test results indicate that the ductility of seismic-damaged SRC columns strengthened with enveloped steel jacket increases with the reduction of the postearthquake damage degree. The results indicate that the calculation formula of shear bearing capacity of SRC columns is feasible. Based on GB50010-2010, ACI318-08, and CSA-04, three different shear models were established, and the calculated values of shear capacity are quite different, and the analysis of the shear strength of RC in the strengthened seismic-damaged SRC column cannot be ignored. The formula is verified, and the calculated results are consistent well with the experimental results.